(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
The occurrence of the diamond squid Thysanoteuthis rhombus in the Colombian Caribbean is recorded for the first time based on one stranded specimen (60 cm mantle lenght) at Morro de Gaira, near Santa Marta.